Risk Prevention Training Of Diabetic Foot Ulcus (Buerger Allen Exercis) In Family And DM Patients (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
There is an increase in diabetic complications every year, therefore prevention is prioritized before complications such as diabetic foot ulcers occur. Many studies have been conducted related to the prevention of diabetic foot ulcers with Buerger Allen exercise which has a significant impact on improving peripheral circulation. The activity aimed to socialize the prevention of diabetic foot ulcers with Buerger Allen exercise. This activity was carried out in March 2021 in collaboration with the Public Health Center of Sungai Raya District as a health service that oversees the location of the activity. The target population in this activity are those who have a history of diabetes mellitus or diabetic foot ulcers or have a family with diabetic foot ulcers. The participants were given knowledge about preventing diabetic foot ulcers by means of the Buerger Allen exercise.